Temporal variation in bacterial and methanogenic communities of three full-scale anaerobic digesters treating swine wastewater - Han, Gyuseong; Shin, Seung Gu; Cho, Kyungjin; Lee, Joonyeob; Kim, Woong; Hwang, Seokhwan (Springer Verlag, 2019)
To investigate the effects of temporal variations of process parameters on microbial community structures in the two types of full-scale anaerobic digester treating swine wastewater, three full-scale anaerobic digesters were monitored. An anaerobic filter (AF)-type digester located in Gong-Ju (GJ) showed the highest COD removal among three digesters and maintained stable efficiency. A digester in Hong-Seong (HS) was of the same type as it GJ and showed improved efficiency over the sampling period. A continuously stirred tank reactor (CSTR)-type digester in Soon-Cheon (SC) showed decreasing efficiency due to a high residual concentration of VFAs and NH4+. These process efficiencies were closely correlated to the Simpson indices of the methanogenic communities. Genera Bacillus, Methanosaeta, and Methanospirillum that have filamentous morphology were dominant in both AF-type digesters, but genera Acholeplasma, Methanosarcina, and Methanoculleus that have spherical or coccoid morphology were dominantly abundant in the CSTR-type digester. Correlation between populations suggests a possible syntrophic relationship between genera Desulfobulbus and Methanosaeta in digesters GJ and HS.